Two‐Step Tandem Catalysis for High‐Efficiency Ammonia Synthesis Via Nitrate Reduction on Anion‐Intercalated CoNi LDH and Cu/Cu2O - Changzheng Lin; Weijia Li; Hao Chen; Jiangtao Feng; Mengyuan Zhu; Jinwen Shi; Mingtao Li; Bo Hou; Zhenyu Wang; Xin Chen; Jia Liu; Wei Yan (Advanced Science)
Abstract Ammonia is essential across industry, agriculture, and as a future carbon‐free energy carrier. Electrocatalytic nitrate reduction (NitRR) offers a sustainable path for removing nitrate contaminants from wastewater and groundwater while using abundant nitrate ions as nitrogen sources under eco‐friendly conditions. However, the NitRR pathway, which involves sequential reactions, poses challenges in synchronizing the rate of nitrate‐to‐nitrite conversion with the subsequent reduction of nitrite to ammonia, particularly as the initial reduction step is rate‐limiting. This study presents a CoNi layered double hydroxide (LDH) approach to finely control hydrogen radical (*H) supply, paired with Cu/Cu2O redox coupling, to achieve optimal rate matching. CoNi LDH is engineered with various anion intercalations (NO3−, Cl−, SO42−, MoO42−, WO42−) to regulate *H capacity. By integrating Cu/Cu2O and CoNi LDH, tandem kinetic descriptors, including a volcano curve, are employed to predict rate constants, facilitating ideal kinetic matching for efficient ammonia synthesis. The optimized MoO4‐CoNi LDH/CuO NW/CF electrode demonstrated exceptional performance, achieving a 99.78% Faraday efficiency, a yield of 1.12 mmol cm−2 h−1 at −0.2 V vs. RHE, and robust 14‐h stability. The model descriptors effectively elucidated the kinetic pathway, linking reaction rates and factors impacting ammonia production.